PRAMUWISATA DI KOTA MANADO - Sampelan, Shinta N. (Universitas Sam Ratulangi, 2015)
Tourism is one of the sector become the most potential for income countries and regions. In terms of serve the needs of tourists then provided basic facilities tourism. While to promote tourism and marketing role of the government and the community is highly important. Guidance as the elements necessary in tourism destination guide and markets. Because the sustainability of the tourism industry in Kota Manado not separated from the involvement of a guidance. Research objectives, to know life guidance in Kota Manado as individuals and institutions also representation local culture of the people attached to a guidance. The results of research it turns out that a profession guidance open to other professional which is still moving in the tourism as vocational teachers at the school, a lecturer at the college the science of tourism, hospitality employees, students and citizens local inhabiting an area of tourism around an object. The attraction to becoming a guidance in addition to the demands of a profession that is having a hobby traveling, and can get more income. Keywords: guidance, torism, profession